#TITLE_ALTERNATIVE# - MARTIN PRADIPTA (NIM : 13713062), JONATHAN
Manganese steels are commonly used for abrasive wear components because they can undergo a martensitic transformation when the surface undergoes plastic deformation. To improve resistance to cracks, toughness should be improved. The usual heat treatment process for steel in as-cast conditions is a one-stage heat treatment process at 1100℃ followed by a rapid colling process. In this study, four types of two-stage heat treatment have been performed. In the first and second heat treatment, the first stage heating was carried out at temperatures of 5950C and 620℃ for 10 hours, followed by a second stage heating performed at 980℃ for 2 hours, then a quenching was performed. Meanwhile, in the third, fourth and fifth heat treatments, the first stage heating was carried out at 700 ℃, 675 ℃, and 650 ℃ for 3 hours, followed by a second stage heating performed at 1000 ℃ for 1.5 hours, then a quenching was performed. The comparison of the toughness ratio of the heat treated tensile sample test results showed that the two-stage heat treatment with the first stage heating at 675 ℃ for 3 hours followed by the second stage heating at 1000 ℃ for 1.5 hours resulted in the best toughness ratio.